Decision support system of employee performance evaluation - Fitriana A.; Nguyen P.T.; Rema Devi S.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Employee Performance Evaluation at CV Artha Mandiri Pringsewu is still done manually, without a computerized system, so that it faces obstacles to obtain actual and accurate information. In order to be successful in business today, CV. Artha Mandiri needs information system that can support decision making and various information. Problems that often occur in the process of employee performance appraisal include the decision-making subjectivity, especially if several existing employees have abilities that are not much different. The use of decision support systems is a solution to reduce subjectivity in decision making designed with Visual Basic 6.0 programming, The calculations were performed on all criteria for all employees, so it is expected that employees with the best abilities are selected. Decision support system is supported by a descriptive method in the development of system software with Waterfall model. The calculation process is carried out to determine employee recommendations in the Promotion System based on 3 aspects namely Intellectual Capacity, Work Attitude and Behavior. The result of this process is employee ranking. This ranking is the basis for decision makers to choose employees who are suitable in the vacant positions that are expected to help evaluating the performance of employees at CV Artha Mandiri. BEIESP.